2009
DOI: 10.1086/605593
|View full text |Cite
|
Sign up to set email alerts
|

Gram‐Negative Prosthetic Joint Infections: Risk Factors and Outcome of Treatment

Abstract: GN PJI represents a substantial proportion of all occurrences of PJI. Debridement alone has a high failure rate and should not be attempted when the duration of symptoms is long. Resection of the prosthesis, with or without subsequent reimplantation, as a result of GN PJI is associated with a favorable outcome rate that is comparable to that associated with PJI due to GP pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
167
4
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(197 citation statements)
references
References 17 publications
18
167
4
4
Order By: Relevance
“…Although several studies, including the present study, have demonstrated that MRSA is reduced in patients with vancomycin, no studies to our knowledge have observed a reduced rate of Gram-positive organism. This finding can likely be explained by the narrower coverage of vancomycin compared with cefazolin and is important because infection with organisms other than Gram-positives such as atypical organisms and Gramnegative infection has been associated with poor treatment outcomes [10,17]. Because of the potential for narrower coverage, another antibiotic can be added such as cefazolin or teicoplanin, which is commonly done in Europe, or monotherapy with antibiotics of broader coverage such as aztreonam, levofloxacin, or clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies, including the present study, have demonstrated that MRSA is reduced in patients with vancomycin, no studies to our knowledge have observed a reduced rate of Gram-positive organism. This finding can likely be explained by the narrower coverage of vancomycin compared with cefazolin and is important because infection with organisms other than Gram-positives such as atypical organisms and Gramnegative infection has been associated with poor treatment outcomes [10,17]. Because of the potential for narrower coverage, another antibiotic can be added such as cefazolin or teicoplanin, which is commonly done in Europe, or monotherapy with antibiotics of broader coverage such as aztreonam, levofloxacin, or clindamycin.…”
Section: Discussionmentioning
confidence: 99%
“…In the last few decades, treatment of these infections has become more difficult, mainly because S. aureus develops mechanisms of resistance to the antibiotics used in the treatments [36,37]. While for the Gram-negative, the most tested was E. coli, which, despite the reduced number in the cause of this type of infection, is a relevant group in clinical practice, presenting a difficulty in its treatment [38].…”
Section: Biomaterials -Physics and Chemistry -New Editionmentioning
confidence: 99%
“…They found that conservative treatment of Gram-negative infection by debridements was associated with a lower success rate than treating Gram-positive arthroplasty infections (27 vs 47% remission). However, this difference vanished when a twostage exchange was performed [10].…”
Section: Introductionmentioning
confidence: 96%
“…P. aeruginosa accounts for an absolute minority of all osteoarticular pathogens [1], and most reports are either case series involving around 20-30 cases [9][10][11][12][13] or even less [14][15][16][17][18][19][20][21][22][23][24][25][26][27]. Moreover, these reports subsume P. aeruginosa under other Gram-negative pathogens [9,12,13,19], including anaerobes [10,28], and lack adjustment for case mix [9,10,19,21]. Often, outcome comparisons of osteoarticular infections due to P. aeruginosa with Gram-positive pathogens are almost non-existent [10,28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation